Redescription of Gedea pinguis Cao & Li, 2016 (Araneae: Salticidae) with the first record for Vietnam - Hoang, Quang Duy; Phan, Quoc Toan; Vo, Van Minh (Academia Journal of Biology, 2024)
The jumping spider species Gedea pinguis Cao & Li, 2016 is newly recorded from Vietnam and redescribed based on the sole male specimen. A detailed redescription, illustrations of the copulatory organs, and somatic features, along with an updated distribution map are provided. DNA barcode derived from the mitochondrial cytochrome c oxidase subunit I (COI) gene of the species G. pinguis from Vietnam is also included for future use and to compare the genetic distances with Gedea cf. tibialis Zabka, 1985 from Malaysia. With the addition of a new record, the genus Gedea Simon, 1902 in Vietnam now reaches 3 species, but doubts arise regarding the conspecificity of the two opposite sex species, Gedea tibialis Żabka, 1985 (male) and Gedea typica (Żabka, 1985) (female), as they share the same type locality. Additionally, a dichotomous key to all Gedea species is also given in this study.